2001
DOI: 10.1080/02652030010006104
|View full text |Cite
|
Sign up to set email alerts
|

Natural occurrence of aflatoxins in Korean meju

Abstract: Aflatoxin B1 (AFB1) was found in 35 of 60 (58.3%) meju samples with an average concentration of 7.3 ng/g by ELISA. Contamination of AFB1 was confirmed in 25 of 60 samples (41.6%) using HPLC, with an average concentration of 6.9 ng/g. Mean recoveries from meju ranged from 107% to 170% for AFB1 using ELISA at a spiking range of 1 to 50 ng/g. Over the same range, recoveries using HPLC were from 70% to 83%. The levels of AFB1 determined by ELISA and by HPLC demonstrated a close relationship between the two methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 9 publications
1
17
0
1
Order By: Relevance
“…Aflatoxins, the mycotoxins produced mainly by A. flavus and A. parasiticus, represent a worldwide threat to public health due to their frequent contamination in food and feed (Ali et al, 2005). During the fermentation process of Korean traditional soybean fermented foods including meju, doenjang, and kanjang, contamination with A. flavus or A. parasiticus can ruin the taste and odor of the product (Bae et al, 2003;Kim & Roh, 1985;Kim et al, 2001;Munimbazi & Bullerman, 1998;Ok et al, 2007;Park et al, 2001). Iturin is a cyclolipopeptide containing seven residues of a-amino acids (L-Asn, D-Tyr, D-Asn, L-Gln, L-Pro, D-Asn, and L-Ser) and one residue of a b-amino acid (Grau et al, 2000).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Aflatoxins, the mycotoxins produced mainly by A. flavus and A. parasiticus, represent a worldwide threat to public health due to their frequent contamination in food and feed (Ali et al, 2005). During the fermentation process of Korean traditional soybean fermented foods including meju, doenjang, and kanjang, contamination with A. flavus or A. parasiticus can ruin the taste and odor of the product (Bae et al, 2003;Kim & Roh, 1985;Kim et al, 2001;Munimbazi & Bullerman, 1998;Ok et al, 2007;Park et al, 2001). Iturin is a cyclolipopeptide containing seven residues of a-amino acids (L-Asn, D-Tyr, D-Asn, L-Gln, L-Pro, D-Asn, and L-Ser) and one residue of a b-amino acid (Grau et al, 2000).…”
Section: Discussionmentioning
confidence: 96%
“…For example, aflatoxins can cause liver cancer in animals and humans when ingested as contaminants in feeds or food (Moyne, Shelby, Cleveland, & Tuzun, 2001). Aflatoxins are produced by certain strains of Aspergillus including Aspergillus flavus, Aspergillus parasiticus, Aspergillus nomius, and Aspergillus tamarii, and are known contaminants during fermentation of the soybean products meju, doenjang, and kanjang (Bae, Kwak, Park, Kim, & Shon, 2003;Kim & Roh, 1985;Kim et al, 2001;Ok et al, 2007;Park, Kang, Oh, & Chung, 2001). Previous studies reported that isolation of Bacillus sp.…”
Section: Introductionmentioning
confidence: 98%
“…Data for samples related to intoxications in laboratory animals or referring to mouldy food were also removed from the data set. Therefore, the following occurrence data were chosen: in barley (Park et al 2002), barley-based foods (Park et al 2002), corn (Shon et al 1997, Park et al 2002, corn-based foods (Park et al 2002), meju (Kim et al 2001), and rice (Shon et al 1997).…”
Section: Afb 1 Intake Estimatesmentioning
confidence: 99%
“…A direct competitive ELISA method for AFB 1 was performed, as developed by Kim et al (2001). In summary, the method involved extraction of the samples with methanol-water (8:2, v/v), centrifugation of the extract, and dilution of the supernatant with 0.02 M Tris-buffered saline containing 0.05% Tween 20 (TBST, pH 7.4).…”
Section: Samplesmentioning
confidence: 99%
“…In addition, soybeans are used in fermented foods such as Doeanjang (soybean paste) and Ganjang (soy sauce). In many previous studies, AFs have been detected in raw material and fermented soybean products such as Doenjang, Meju, and Miso (Bae, Kwak, Park, Kim, & Shon, 2003;Kim et al, 2001;Tanaka, Goto, Manabe, & Matsuura, 2002). Most soybean-based food involves the soaking, heating, and steaming of soybeans to reduce the cooking time.…”
Section: Introductionmentioning
confidence: 96%